A biochar-based amendment improved cadmium (Cd) immobilization, reduced its bioaccumulation, and increased rice yield - Han, Junnan; Wu, Donghai; Yang, John; Shi, Yuan; Abid, Ghassen; Wang, Lingjun; Li, Zhengguo (Frontiers in Environmental Science, 2024)
Cadmium (Cd) contamination of soil threatens human health, food security, and ecosystem sustainability. The in situ stabilization of Cd has been recognized as a potentially economical technology for the remediation of Cd-contaminated soil. Recently, biochar (BC) and activated carbon (AC) have received widespread attention as eco-friendly soil amendments that are more beneficial for plant growth, soil health, and remediation of contaminated soil. An experiment was performed in a paddy field to investigate the effects of two different types of BC (maize straw biochar and bamboo biochar) and AC (coconut shell activated carbon) in combination with rape organic fertilizer (R), calcium magnesium phosphate fertilizer (P), and fulvic acid (F), respectively, on soil Cd immobilization, Cd accumulation in rice, and yield. The results indicated that the BC/AC-based amendments reduced soil bioavailable Cd (DTPA-Cd) and brown rice Cd by 9.58%–27.06% and 19.30%–71.77%, respectively. The transformation of exchangeable Cd (Ex-Cd) to carbonate-bound Cd (Ca-Cd), Fe-Mn oxide bond (Ox-Cd), and residual (Re-Cd) in soil accounted for the mitigation of Cd uptake and enrichment by rice. Additionally, BC-/AC-based amendments altered soil physicochemical properties, which significantly increased the soil pH and cation exchange capacity (CEC), total nitrogen (TN), total phosphorus (TP), soil organic carbon (SOC), and dissolved organic carbon (DOC), directly promoting soil health. All BC-/AC-based amendments significantly increased FeIMP and MnIMP concentrations by 47.31%–160.34% and 25.72%–73.09% in the Fe/Mn plaque (IMP), respectively. Maize straw and bamboo biochar-based amendments significantly increased rice yield by 10.46%–20.41% and 9.94%–16.17%, respectively, while coconut shell-activated carbon severely reduced rice yield by 65.06%–77.14%. The correlation analysis revealed that leaf Cd and IMP primarily controlled Cd uptake by rice, and soil pH, Eh, CEC, SOC, IMP, and TP influenced DTPA-Cd in soil. This field study demonstrated that maize straw and bamboo biochar-based amendments not only reduced soil DTPA-Cd in paddy fields but also decreased the accumulation of Cd in brown rice, as well as improved rice yield, which has potential application in Cd-contaminated agriculture fields. Coconut shell-activated carbon severely decreased rice yields, which is not appropriate for rice production.